Ingestive peptides - Banks, William (Henry Stewart Talks, 2008)
Ingestive peptides, Transport across the blood-brain barrier, Relation to obesity, Control of transporter and implications for body weight control, Ghrelin and its relation to the blood-brain barrier and body weight control